Gothic Transformations and Remediations: An Intertextual Analysis of Ann Radcliffe’s “The Romance of Forest” - Nimra Ijaz Cheema; Farwa Akhter (Social Science Review Archives, 2025)
Interplay between texts is mandatory to literary advancements, and Ann Radcliffe exemplifies this through its rich intertextual connection with Gothic and Romantic rituals in her novel “The Romance of the Forest”. This paper evaluates a novel’s implicit intertextuality, pursuing how Radcliffe establishes references to prior literary works, cultural narratives, and philosophical texts to generate meaning and reader interpretation. Radcliffe both sustains and defies genre constraints by evoking gothic precedents like romantic masterpieces such as Samuel Richardson’s “Clarissa” and Horace Walpole’s “The Castle of Otranto”. A qualitative, intertextual analysis is implied, applying close reading and comparative literary methods to expose subtle antecedents and structural influences within the novel. “The Death of the Author” by Roland Barthes provides conceptual insights, and Michael Riffaterre’s concepts on implicit intertextuality lay down the critical framework for assessing the novel's intertwined textuality. The novel’s adaptable plot structure allows for multiple interpretations, resisting rigid receptions. It can be read as a romantic introspection on nature and the sublime, a feminist critique of male-dominated oppression, or a psychological analysis of terror and identity. Her work is situated within an era of nurturing gothic discourse due to her use of symbolic motifs and shattered storylines that resonate with deeper literary traditions. This study showcases the reader’s active involvement in constructing literary truths; underscoring the concept that texts are never isolated instead its always in discussion with one another.